Dispersion Analysis of Twist-Symmetric Dielectric Waveguides - Pilar Castillo-Tapia; Kwinten Van Gassen; Qiao Chen; Francisco Mesa; Zvonimir Sipus; Oscar Quevedo-Teruel (Photonics, 2021)
We propose a circular twist-symmetric dielectric waveguide that is polarization-selective. In the practical implementation of optical fibers, a selective circular polarization is more convenient than its linearly polarized counterpart where previous knowledge of the emitted polarization from the transmitter is unknown. The analysis of the waveguide was conducted with three methods: an eigenmode approach, simulation of a truncated structure, and the so-called multimodal transfer-matrix method (MMTMM). The presented simulations demonstrate that the operational band can be manipulated by tuning the parameters of the structure. Furthermore, the MMTMM allows for a direct and accurate calculation of the attenuation constant of the rejected circular polarization.